Pengaruh Bubur Kacang Hijau Terhadap Kecukupan Air Susu ‎Ibu (ASI)‎ - Zilfi Yola Pitri; Adiva Syafira Arla (Indra Institute Research & Publication, 2023)
Mother's Milk (ASI) is a single food source for babies for the first 6 months of life. The Indonesian government has issued regulations regarding exclusive breastfeeding stated in government regulation (PP) No. 33 of 2012 concerning exclusive breastfeeding. This study aims to look at the effect of porridge green beans on the adequacy of Mother's Milk (ASI) in postpartum mothers. This type of research is a Quasi Experiment with a One-Group Pre-Test-Post-Test design. The population of all postpartum mothers amounted to 30 people with a purposive sampling technique of 10 people. Univariate analysis results found that the average milk production before being given porridge mung beans was 5.20 times and increased after being given porridge mung beans that was 11.90 times. The results of the statistical test found that there was an effect of giving green bean porridge to the production of Breast Milk (ASI) in postpartum mothers (p = 0,000). From these data it was concluded that the average adequacy of breast milk before being given porridge of green beans to postpartum mothers was 5.20 times. mung beans on the adequacy of Mother's Milk (ASI) in postpartum mothers, It is recommended that this study can be used as a comparison and guide in conducting research in other subjects as well as adding material to knowledge, experience and can be developed in midwifery.